2014
DOI: 10.3329/jom.v15i1.19855
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Rheumatological Disorders: A Clinic-based Study

Abstract: Conclusion:Degenerative joint and spine diseases were more common but as an individual disease rheumatoid arthritis was the most prevalent condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…19,[22][23] Our study found RA in 76.23%, AS in 13.33 %, PsA in 4.35%, gout in 3.48% and reactive arthritis in 2.6% cases among inflammatory joint diseases that was different from a previous study. 15 In our study, female were predominant in RA while males were more prone to develop other inflammatory arthritis.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…19,[22][23] Our study found RA in 76.23%, AS in 13.33 %, PsA in 4.35%, gout in 3.48% and reactive arthritis in 2.6% cases among inflammatory joint diseases that was different from a previous study. 15 In our study, female were predominant in RA while males were more prone to develop other inflammatory arthritis.…”
Section: Discussionsupporting
confidence: 47%
“…Other studies from Bangladesh, Italy, Malaysia and Congo showed much less prevalence of SLE but females were predominant in that studies. 15,[24][25][26][27] Osteoporosis was present in 12% cases, which was lower than other studies from Nepal and Belgium 16,17 as endocrinologists manage many osteoporosis cases.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Reports from India, Bangladesh and abroad show that the female-to-male ratio is between 8:1 and 12:1. 1,45,46 These patients have more than one system involved at presentation. 28 Cutaneous manifestations are the commonest presenting features.…”
Section: Discussionmentioning
confidence: 99%
“…Degenerative joint disease (DJD) included osteoarthritis knees (33.67%, 12.66%), lumbar spondylosis (23%, 17.33%), cervical spondylosis (14%,13.66%) in both groups comprised the major bulk of problems among patients with MSK problems which supports other studies. 12,13 In diabetic group 20% patient were of frozen shoulder and in non-diabetic it was 5.66%. Ray et al 14 studied 100 diabetic patients and found 18% patients had frozen shoulder which supports our study.…”
Section: Discussionmentioning
confidence: 99%